Perbaikan Mekanisme Otomasi Toolpost Mesin Bubut di SMK Karya Teknika - Pratama, Riza Arif; Harwijayanti , Widyanita; Ikhsan, Muhammad; Setiajit, Sahid Bayu (Pusat Penelitian dan Pengabdian Masyarakat, 2025)
The community service activity conducted by the Aircraft Maintenance Engineering (TPP) team of UTP took place at SMK Karya Teknika, located in Colomadu, Karanganyar Regency. The school encountered an issue with the malfunctioning automation system of the tool post on its lathe machine. This malfunction disrupted students' practical activities during machine operation. The repair process involved fabricating a new half-nut, as the original component had worn out based on inspection and problem identification. The replacement half-nut was made using bronze material due to its durability against friction and resistance to corrosion. This choice ensures a longer service life for the component, making it suitable for continuous student practice sessions. After replacing the worn-out part with the newly manufactured half-nut, the lathe machine resumed regular operation, thereby restoring the smooth running of teaching and learning activities. SMK Karya Teknika expressed its appreciation for the community service efforts in addressing the lathe machine issue.